2021
DOI: 10.1093/humrep/deab165
|View full text |Cite
|
Sign up to set email alerts
|

The cyto-protective effects of LH on ovarian reserve and female fertility during exposure to gonadotoxic alkylating agents in an adult mouse model

Abstract: STUDY QUESTION Does LH protect mouse oocytes and female fertility from alkylating chemotherapy? SUMMARY ANSWER LH treatment before and during chemotherapy prevents detrimental effects on follicles and reproductive lifespan. WHAT IS KNOWN ALREADY Chemotherapies can damage the ovary, resulting in premature ovarian failure and reduced fertility in cancer survivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 62 publications
(77 reference statements)
1
12
0
Order By: Relevance
“…In previous papers, we reported a significant and unexpected protective effect of luteinizing hormone (LH) against the cisplatin (CIS)-induced apoptosis of the primordial follicle pool in prepubertal ovaries [ 2 ]. Moreover, we confirmed such LH protection both in prepubertal and adult animals [ 2 , 3 ]. In the in vitro system, we also found that LH treatment of the ovarian tissues generated molecular signals in the ovarian somatic cells that, through the activation of PI3K/AKT and cAMP/PKA pathways in the oocytes, prevented their apoptosis [ 2 ].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…In previous papers, we reported a significant and unexpected protective effect of luteinizing hormone (LH) against the cisplatin (CIS)-induced apoptosis of the primordial follicle pool in prepubertal ovaries [ 2 ]. Moreover, we confirmed such LH protection both in prepubertal and adult animals [ 2 , 3 ]. In the in vitro system, we also found that LH treatment of the ovarian tissues generated molecular signals in the ovarian somatic cells that, through the activation of PI3K/AKT and cAMP/PKA pathways in the oocytes, prevented their apoptosis [ 2 ].…”
Section: Introductionsupporting
confidence: 71%
“…In the present work, our main aim was to characterize the extracellular in vitro microenvironment in which the oocytes within the primordial/primary follicles underwent apoptosis induced by CIS or were, for the most part, protected by concomitant administration of LH [ 2 , 3 , 6 ]. Moreover, we looked to confirm the ability of early postnatal ovaries to respond to LH stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All sections were observed with a light microscope (Olympus VS120, Olympus, Tokyo, Japan) and digitized with software VS-ASW (Olympus). The ovarian follicles were classified into 4 types as described previously 21 , 22 : primordial follicles, having one layer of flattened pre-granulosa cells surrounding the oocyte; primary follicles, showing one layer of cuboidal granulosa cells; secondary follicles, containing at least two layers of granulosa cells; and atretic follicles, exhibiting disorganized, apoptotic, and degenerative changes in the eosinophilic granulosa cells of the ooplasm, contraction and clumping of the chromatin, and wrinkling of the oocyte nuclear membrane. The endometrial thickness was measured from the luminal surface to the beginning of the circular smooth muscle layer with ImageJ software, as previously reported 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Jiang et al showed that only a single injection of BUL and CTX can cause accelerated follicles depletion in mice, mimicking the process of ovarian aging (6). This mouse model has been widely adopted as a mouse model of POI for study (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%